1994
DOI: 10.1128/aem.60.6.2107-2112.1994
|View full text |Cite
|
Sign up to set email alerts
|

Pectinolytic Enzymes from Actinomycetes for the Degumming of Ramie Bast Fibers

Abstract: Actinomycetes isolated from 10 different soil and compost samples were screened for production of pectinolytic enzyme activities when grown on pectin-containing solid and liquid media. Pectinolytic enzymes, detected by using plate diffusion tests with a medium containing ramie (Boehmeria nivea) plant material as the sole carbon source, were mainly pectate lyases, but low activities of pectinesterases were also observed. Polygalacturonases and polymethylgalacturonases were not produced. Multiple forms of pectat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(32 citation statements)
references
References 27 publications
1
29
0
2
Order By: Relevance
“…Every pectinolytic microbes found in our study had cellulolytic activity. Brühlmann, and his colleague 36 reported that cellulolytic activities were always found to be associated with pectinolytic and xylanolytic activities.…”
Section: Comparison Of Individual and Consortial Enzyme Activity Strmentioning
confidence: 99%
“…Every pectinolytic microbes found in our study had cellulolytic activity. Brühlmann, and his colleague 36 reported that cellulolytic activities were always found to be associated with pectinolytic and xylanolytic activities.…”
Section: Comparison Of Individual and Consortial Enzyme Activity Strmentioning
confidence: 99%
“…Pectic substances are ubiquitous in the plant kingdom and their efficient utilization could enhance the economic competitiveness of bioconversion processes intended to compete with conventional industrial processes (Kapoor et al , 2001. Therefore nowadays a significant interest in the degradation of pectic substances has been generated, which is evident from a vast range of industrial applications such as degumming of bast fibres (Sharma 1987;Baracat et al 1989;Bruhlmann et al 1994;Kapoor et al 2001), treatment of alkaline pectic waste water (Tanabe et al 1988), and extraction, clarification and depectinization of fruit juices (Alkorta et al 1998). The enzymes that hydrolyse pectic substances are broadly termed as pectinases, which include polygalacturonase, pectin esterase, pectin lyase and pectate lyase, named on the basis of their mode of action (Singh et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…种类与化学键型多样, 主要包括聚半乳糖醛酸(homogalacturonan, HG)、木糖聚半乳糖醛酸(xylogalacturonan, XG)、鼠李聚半乳糖醛酸(rhamnogalacturonan, RG) 3种类型 [3] . 放线菌分泌的果胶酶主要是果胶裂解 酶, 以及少量的果胶酯酶, 常常缺乏聚半乳糖醛酸酶 和聚半乳糖醛酸甲酯水解酶等 [22] . 因此, 相关放线菌 对于富含果胶和木葡聚糖的双子叶类植物的降解能 力应该较弱 [21] .…”
Section: 果胶是植物细胞壁中结构最为复杂的多糖 多糖unclassified